Sponsorship by food and beverage companies in soccer: an analysis of the 2019 Copa América - Larissa Cardoso de Miranda Araujo; Juliana de Paula Matos; Paula Martins Horta (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To identify the sponsorship by food and beverage companies of the teams participating in the 2019 Copa América Soccer Cup and associate this sponsorship with characteristics of the teams and their respective countries. METHODS The sponsors of the 10 teams participating in the 46th edition of the Copa América were identified. These entities were classified into (i) food companies, (ii) alcoholic beverage companies, and (iii) other segments. The food companies were classified according to their products, according to the NOVA classification. In addition, data on the number of titles previously won by the teams in the Copa America and the World Cup were obtained, as well as data on the countries' Human Development Index, annual per capita sales of ultra-processed foods, and annual per capita consumption of alcoholic beverages. RESULTS A total of 89 sponsorships were identified for the 10 teams studied, some of these supporting two or more teams. Eighteen percent of the sponsors were food companies, with 12.4% being ultra-processed foods. The alcoholic beverage category represented 7.9% of the sponsors. Ultra-processed beverage and alcoholic beverage companies sponsored seven of the 10 teams studied. We noted higher participation of ultra-processed foods company sponsors in teams from countries with higher Human Development Index, sales of ultra-processed foods, and number of Copa América and World Cup titles. The sponsorship by alcoholic beverage companies was higher for teams from countries with lower Human Development Index, alcohol consumption, and number of Copa América and World Cup titles. CONCLUSION A significant presence of ultra-processed food and alcoholic beverage companies as sponsors of South American soccer teams was noted, along with the fact that sport performance characteristics of the teams and socioeconomic and market issues of the countries are associated with the occurrence of sponsorship.